Language for International Communication: Linking Interdisciplinary Perspectives: Language for Specific Purposes in the Era of Multilingualism and Technologies. Volume 4 - (:unkn) unknown (University of Latvia Press, 2023)
This collection contains papers delivered at the 5th International symposium Language for International Communication: Linking Interdisciplinary Perspectives: Language for Specific Purposes in the Era of Multilingualism and Technologies (LINCS 2022) held on-line from the University of Latvia, Latvia, on April 28–29, 2022.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics; Spanish; French; English; Teaching